2018
DOI: 10.3390/galaxies6040137
|View full text |Cite
|
Sign up to set email alerts
|

Faraday Tomography of the SS433 Jet Termination Region

Abstract: A jet termination region provides us with useful information about how a jet interacts with the interstellar medium. Identifying the strength and orientation of magnetic fields at the terminal is crucially important to understanding the mechanism of cosmic-ray acceleration. In this article, we report results of our Faraday-tomography analysis of the eastern region of the radio nebula W50, where a jet from the microquasar SS433 seems to terminate. We apply QU-fitting, a method of Faraday-tomography, to data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…SS 433 is a (so far) unique Galactic object consisting of a stellar jet protruding through the SNR W50. Haruka Sakemi obtained ATCA observations at 2.3 − 3.0 GHz of SS 433 and showed that there is a strong polarized filament behind the SS 433 jet head, and weaker filaments behind it possibly indicating a helical magnetic field [41]. Faraday Tomography reveals a complex pattern of Faraday depth components from 0 to ∼ 300 rad m −2 .…”
Section: Magnetic Fields In Galactic Objectsmentioning
confidence: 99%
“…SS 433 is a (so far) unique Galactic object consisting of a stellar jet protruding through the SNR W50. Haruka Sakemi obtained ATCA observations at 2.3 − 3.0 GHz of SS 433 and showed that there is a strong polarized filament behind the SS 433 jet head, and weaker filaments behind it possibly indicating a helical magnetic field [41]. Faraday Tomography reveals a complex pattern of Faraday depth components from 0 to ∼ 300 rad m −2 .…”
Section: Magnetic Fields In Galactic Objectsmentioning
confidence: 99%
“…In addition, while modern radio polarimetry adopts Faraday tomography to estimate RM (e.g., Van Eck et al 2017;Sakemi et al 2018, Cantwell et al 2020), DING's effects on Faraday dispersion function (FDF) is not paid much attention (Kim et al 2016). Clarification of DING's effects is crucial for exploring galactic (Sun et al 2008;Oppermann et al 2012;Akahori et al 2013;Xu & Han 2014a;Hutschenreuter et al 2021) and intergalactic (Akahori & Ryu 2010;Akahori & Ryu 2011;Hammond et al 2012;Vernstrom et al 2019;O'Sullivan et al 2020) magnetic fields with future large surveys.…”
Section: Introductionmentioning
confidence: 99%